2018
DOI: 10.1186/s12890-018-0705-6
|View full text |Cite|
|
Sign up to set email alerts
|

The all age asthma cohort (ALLIANCE) - from early beginnings to chronic disease: a longitudinal cohort study

Abstract: BackgroundAsthma and wheezing disorders in childhood and adulthood are clinically heterogeneous regarding disease presentation, natural course, and response to treatment. Deciphering common disease mechanisms in distinct subgroups requires harmonized molecular (endo-) phenotyping of both children and adult patients with asthma in a prospective, longitudinal setting.MethodsThe ALL Age Asthma Cohort (ALLIANCE) of the German Center for Lung Research (DZL) is a prospective, multi-center, observational cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
0
53
0
1
Order By: Relevance
“…The "lung-and small airway-on-a-chip" technologies will rapidly contribute to filling the current translational gap in lung research and advance drug development, biomarker identifica- between age groups is also interesting. The ALL Age Asthma Cohort (ALLIANCE) offers a unique, integrative, and interdisciplinary framework with a comprehensive molecular approach in a prospective and identical fashion across ages in order to identify biomarkers and predictors for distinct childhood wheeze and asthma trajectories as well as their further course during adulthood (125). Taken together, the implementation of precision medicine in clinical practice should consider insight into high-risk groups indicated by public health studies, including those linked to age, sex, and ethnicity.…”
Section: Tissue Responses and Disease Endotypesmentioning
confidence: 99%
“…The "lung-and small airway-on-a-chip" technologies will rapidly contribute to filling the current translational gap in lung research and advance drug development, biomarker identifica- between age groups is also interesting. The ALL Age Asthma Cohort (ALLIANCE) offers a unique, integrative, and interdisciplinary framework with a comprehensive molecular approach in a prospective and identical fashion across ages in order to identify biomarkers and predictors for distinct childhood wheeze and asthma trajectories as well as their further course during adulthood (125). Taken together, the implementation of precision medicine in clinical practice should consider insight into high-risk groups indicated by public health studies, including those linked to age, sex, and ethnicity.…”
Section: Tissue Responses and Disease Endotypesmentioning
confidence: 99%
“…In the adult arm of the ALLIANCE asthma cohort we prospectively recruited patients with an established diagnosis of asthma [7] across different severity grades and inflammatory phenotypes as identified by FeNO, blood and sputum differential cell counts [8]. As recently recommended [5], the patients were clinically well characterized, the asthma diagnosis was thoroughly established, and breath VOCs were compared between different asthma phenotypes.…”
Section: Breath Volatile Organic Compounds and Inflammatory Markers Imentioning
confidence: 99%
“…At present, no effective treatments are known that can halt or reverse the changes of airway remodeling and influence lung function [11]. Longitudinal research has indicated that current therapeutic interventions are relatively ineffective in reversing or inhibiting the development of airway changes [8,[12][13][14]. However, an alternative form of treatment may lie in the use of natural products as complementary therapy.…”
Section: Introductionmentioning
confidence: 99%